RANCANG BANGUN PINTU OTOMATIS PADA SHELTER BASE TRANCEIVER STATION (BTS) BERBASIS WEMOS DI MINI MENGGUNAKAN WEB - ., Jheri Mayco Saragih (Jurnal Teknik Elektro Universitas Tanjungpura, 2018)
In this modern world, digital technology is rapidly improving, there is much automation being developed nowadays. The door that is used to be opened manually; now can probably be designed as automated too, so it would ease people in doing various activities and the automation is completed by safety system as well, so the door can only be opened by certain people. With the fast improving technology, the author is trying to apply such technology in automating a web-based door. One of the systems is the Automatic Door Opener System based on mini Wemos D1 using the web. This design was an idea that appeared when the author was doing an internship in PT. Aplikanusa Lintasarta. Such safety system was needed in the shelter room to keep the equipment safe inside the room. A design that could ease the technician’s work was needed in solving the problems of PT Aplikanusa Lintasarta costumers. The shelter has an important function in each of its locations, so a safety system is needed to keep each of the important equipment inside the shelter itself. Because the technician is often doing the rehabilitation in its equipment as well as improvement in the disturbance, the author intention is to help the technicians, so they don’t have to bring the shelter keys anymore and for the shelter safety reason itself. This expected to help in monitoring the door’s condition that can be done without having to directly watch for the shelter’s location directly. To ease the technicians’ work and to make them work more efficiently, a tool to open the shelter door and to monitor the shelter door condition is needed wherever the disturbance location is. The safety system will facilitate the technician that needs to reach the disturbance location especially when he forgot to bring the destined shelter key. A study then is being conducted by making a tool in hopes the PT. Aplikanusa Lintasarta main office which is located in Pontianak is being able to monitor and open the shelter door based on the shelter areas using a web-based automatic door detection system. Keywords: shelter, safety, analog, digital, web